Transformation of marketing communications under the influence of social media evolution - Kondratiuk, Roman (Актуальні питання економічних наук, 2026)
The rapid digitalization of economic activity and the widespread adoption of online platforms have significantly reshaped the system of brand–audience interaction. Networked environments, algorithm-driven feeds, and data-based targeting tools have altered the logic of value promotion, shifting emphasis toward interactivity, personalization, and continuous feedback. These processes necessitate a comprehensive examination of the structural and functional changes in contemporary communication systems, influenced by the development of social networking platforms. The purpose of this study is to systematize the key directions of modernization in promotional instruments amid the expansion of digital platforms and to substantiate transformations in interaction models between businesses and target audiences driven by content algorithmization and user participation. Methods. The research applies general scientific and specialized approaches, including analysis and synthesis to refine the conceptual framework, comparative assessment to identify distinctions between traditional and digital formats of promotion, a structural–functional approach to determine the components of the updated interaction system, and generalization of empirical evidence reflecting current business practices in digital environments. Results. The findings demonstrate a transition from one-way information delivery to multidirectional dialogue with audiences. It is established that the contemporary promotion system is characterized by personalized messaging, the integration of data analytics, the dominance of visual and short-form formats, and the active involvement of consumers in content creation. Algorithmic ranking mechanisms are shown to influence campaign planning and require continuous performance monitoring. The competitiveness of enterprises increasingly depends on their ability to adapt strategic decisions to the dynamics of digital ecosystems and evolving user expectations. Conclusions. The study confirms the emergence of an integrated interaction model combining analytical tools, creative formats, and automated message customization technologies. Further development of promotional practices is associated with deeper personalization, broader adoption of artificial intelligence solutions, and enhanced behavioral data analytics.